Progressive Collapse of RC Box Girder Bridges due to Seismic Actions - Heba A. Mohamed; M. M. Husain; Ayman M. Aboraya (Advances in Civil Engineering)
Most of the recent studies focus on the progressive collapse of ordinary structures due to gravity and blast loads. A few focus on studying progressive collapse due to seismic actions, especially of bridge structures. The past major earthquakes have shown that it is possible to develop improved earthquake-resistant design techniques for new bridges if the process of damage from initial failure to ultimate collapse and its effects on structural failure mechanisms could be analyzed and monitored. This paper presents a simulation and analysis of bridge progressive collapse behavior during seismic actions using the Applied Element Method (AEM) which can take into account the separation of structural components resulted from fracture failure and falling debris contact or impact forces. Simple, continuous, and monolithic bridges’ superstructures were numerically analyzed under the influence of the severe ground motions not considering the live loads. The parameters studied were the superstructure redundancy and the effect of severe ground motion such as Kobe, Chi-Chi, and Northridge ground motions on different bridge structural systems. The effect of reducing the reinforcement ratio on the collapse behavior of RC box girders and the variation of columns height were also studied. The results showed that monolithic bridge models with reduced reinforcement to the minimum reinforcement according to ECP 203/2018 showed a collapse behavior under the effect of severe seismic ground motions. However, changing the bridge structural system from monolithic to continuous or simple on bearing bridge models could prevent the bridge models from collapse.